The effect of Scrophularia striata on cell attachment and biocompatibility of decellularized bovine pericardia - Alizadeh, Morteza; Rezakhani, Leila; Taghdiri Nooshabadi, Vajihe; Alizadeh, Akram (Cell and tissue banking, 2022)
Since using tissue transplantation has faced limitations all over the world, regenerative medicine has introduced decellularized tissues as natural scaffolds and researchers are trying to improve their efficiency and function. In this study, to increase cell attachment and ultimately cell proliferation on decellularized bovine pericardia, scrophularia striata extract was used. Scrophularia striata is an Iranian traditional medicinal plant. For this aim after decellularization of bovine pericardium and analysis of its morphology, it was incubated in scrophularia striata solution. Next, isolated human adipose-derived mesenchymal stem cells were cultured on the tissue. Finally, MTT assay, nitric oxide assay, and scanning electron microscopy observation were performed. MTT showed an increase in cell survival after treating the tissue with the plant extract after 48 h in a dose dependent manner significantly. The survival of cells in 0.5%, 2.5%, and 5% groups was about 5, 10 and 15 folds higher in comparison to control groups, respectively. Additionally, nitric oxide secretion in 2.5% and 5% samples was three and five folds higher than that in control group, respectively. Moreover, SEM observation indicated an impressive and dose-dependent effect of using Scrophularia striata on tissue biocompatibility . The results of this study showed that using Scrophularia striata increased cell viability and cell attachment on decellularized pericardia which could pave the way for the use of natural extracts of medicinal plants to reduce unwanted effects and make desired changes in decellularized tissues.